Miseducating Latina researchers: Challenges and consequences in the field. Issue 4 (December 2016) - Martinez, Isabel
Abstract This article examines how racism in the academy, by virtue of omission of discussions of race and its intercentricity with other forms of subordination, has the potential to endanger Latina researchers conducting fieldwork in familiar and unfamiliar settings. Failure to consider the intersections of race, gender, immigration and other axes of subordination resulted in three incidents of near-violence and intimidation for one Chicana researcher that, while frightening, are instructive for future and current researchers. Arguing that traditional qualitative methods classrooms and texts overlook the particular challenges and risks that Latina and other female researchers of color may face in the field, this article encourages the inclusion of teaching of critical race theory and critical race methodologies when training novice and senior researchers.